Mixed ligand complex: Synthesis, characterization, and investigation of biomedical activity - Elaf A. Mousa; Basim I. Al-Abdaly (مجلة بغداد للعلوم, 2024)
A new complex, CuCl2.2H2O (M), was synthesized to react with melatonin (L1) and one of the amino acids (L-cysteine, L2) in a mole ratio of (1:1:1) (M: L1:L2) to produce the metal complex. The synthesized complex was then characterized using spectral techniques including infrared (FT-IR), thermal analysis (TG), flame atomic absorption (AAS), micro elemental analysis (CHNS), melting point (m.p.) measurement, and determination of chloride. Octahedral geometry was proposed for the complex. The copper complex was paramagnetic and non-electrolyte. The synthesized complex was evaluated as an antibacterial and antifungal agent against Escherchia coli (G-) and Staphylococcus aureus (G+). fungus Candida. The results showed that the copper complex was more active in 10–3 M  than the two ligands; the complex's anti-cancer properties were also evaluated and gave a good result in the test.